Safety and efficacy of selenium compounds (E8) as feed additives for all animal species: sodium selenite, based on a dossier submitted by Retorte GmbH Selenium Chemicals and Metals - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (EFSA Journal, 2016)
Abstract Selenium is a trace element that is essential for vertebrates and involved in a series of vital metabolic functions. Sodium selenite is considered to be a safe and efficacious source of selenium for all animal species/categories. The use of sodium selenite as a source of selenium in animal nutrition is considered to be safe for the consumer, provided that the total maximum authorised content of selenium in complete feed is respected. The additive is considered to be an irritant to the skin, eyes and the respiratory system, and a skin sensitiser. Systemic exposure to selenium could result from dermal contact. Users/workers handling the additive would be exposed to selenium by inhalation at levels which constitute a risk. The use of sodium selenite in animal nutrition up to the maximum authorised content in feed would not raise concerns to the soil compartment, the ground or surface water. Concerning the marine sediments, given the standard aquaculture practices and the low potential maximum concentration of selenium from fish feeds, any impact on the environment is unlikely.